Hydro politics in the arid and semi-arid zones of South American Andes - de Cossío Klüver, Manuel (2021)
According to conventional knowledge, interstate competition to access scarce planetary freshwater sources is likely to become one of the main concerns of governments and the world’s population in the coming decades. If this prediction is fulfilled, the already existing tensions between States could increase when more intense competition is added for the water resources located on their borders. These tensions would become more acute in arid or semi-arid areas, such as the Andes and the South Pacific coast, where there is a chronic shortage of fresh water as well as water stress, where the retreat of glaciers and the pressures that are exerted on limited existing water resources magnify the overall scarcity picture, and thus water stress. This article is part of a study on the emerging water stresses of the use and management of transboundary water resources in arid and semi-arid zones, as well as its impact on the security of the States that share international watercourses. The case of the Silala hydrographic system, located in the puna of the Atacama Desert, will be used to analyze the political factors that could trigger water conflicts, as well as hinder the adoption of cooperative agreements.